2011
DOI: 10.1080/10509674.2011.602472
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into the Effect of Respondent Gender, Victim Age, and Perpetrator Treatment on Public Attitudes Towards Sex Offenders, Sex Offender Treatment, and Sex Offender Rehabilitation

Abstract: In this study the authors examine the effect respondent gender, victim age, and offender treatment programs have upon public attitudes towards sex offenders. A community sample of 235 participants were asked to read a hypothetical vignette involving the sexual assault of a 10-, 15-, or 20-year-old female by a 35-year-old male who subsequently completed either a sex offender treatment or car maintenance program whilst in prison. Respondents then completed three psychometrically sound measures assessing general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 25 publications
3
44
0
Order By: Relevance
“…Similarly, Ferguson and Ireland's (2006) study identified the most negative attitudes toward sex offenders with child victims. Other studies have reported similar findings in that sexual offending against children is deemed the most serious and deserving of harsh punishment (Kernsmith et al, 2009;Rogers, Hirst, & Davies, 2011). Fewer studies have examined the effect of offender age on attitudes toward sex offenders.…”
Section: Victim and Offender Agementioning
confidence: 73%
“…Similarly, Ferguson and Ireland's (2006) study identified the most negative attitudes toward sex offenders with child victims. Other studies have reported similar findings in that sexual offending against children is deemed the most serious and deserving of harsh punishment (Kernsmith et al, 2009;Rogers, Hirst, & Davies, 2011). Fewer studies have examined the effect of offender age on attitudes toward sex offenders.…”
Section: Victim and Offender Agementioning
confidence: 73%
“…Some scholarship has examined rehabilitation and treatment views of college students (e.g., Rogers, Hirst, & Davies, 2011) and in other countries (Brown, 1999;Viki, Fullerton, Raggett, Tait, & Wiltshire, 2012). Some scholarship has examined rehabilitation and treatment views of college students (e.g., Rogers, Hirst, & Davies, 2011) and in other countries (Brown, 1999;Viki, Fullerton, Raggett, Tait, & Wiltshire, 2012).…”
Section: Notesmentioning
confidence: 99%
“…There have, for example, been mixed results regarding how sex influences attitudes, with a number of studies finding that females generally view sex offenders more negatively than males (Beck & Travis, 2004;Brown, Deakin, & Spencer, 2008;Kernsmith et al, 2009). Other studies, however, have reported no significant differences between sexes (Olver & Barlow, 2010;Rogers, Hirst, & Davies, 2011;Sahlstrom & Jeglic, 2008).…”
Section: Attitudes Towards Sex Offendersmentioning
confidence: 99%